The contextual effects of neighbourhood access to supermarkets and convenience stores on individual fruit and vegetable consumption. Issue 3 (13th February 2008) - Pearce, J; Hiscock, R; Blakely, T; Witten, K
Abstract : Background: It is often suggested that neighbourhood access to food retailers affects the dietary patterns of local residents, but this hypothesis has not been adequately researched. We examine the association between neighbourhood accessibility to supermarkets and convenience stores and individuals' consumption of fruit and vegetables in New Zealand. Methods: Using geographical information systems, travel times from the population-weighted centroid of each neighbourhood to the closest supermarket and convenience store were calculated for 38 350 neighbourhoods. These neighbourhood measures of accessibility were appended to the 2002–3 New Zealand Health Survey of 12 529 adults. Results: The consumption of the recommended daily intake of fruit was not associated with living in a neighbourhood with better access to supermarkets or convenience stores. Similarly, access to supermarkets was not related to vegetable intake. However, individuals in the quartile of neighbourhoods with the best access to convenience stores had 25% (OR 0.75, 95% CI 0.60% to 0.93%) lower odds of eating the recommended vegetable intake compared to individuals in the base category (worst access). Conclusion: This study found little evidence that poor locational access to food retail provision is associated with lower fruit and vegetable consumption. However, before rejecting the commonsense notion that neighbourhood access to fruit and vegetables affects personal consumption, research that measures fruit and vegetable access more precisely and directly is required.